Pengaruh Kepemilikan Institusional, Modal Intelektual, Corporate Social Responsibility dan Manajemen Risiko Terhadap Nilai Perusahaan - Ismanto, Juli; Effriyanti, Effriyanti (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2025)
This study examines the effect of institutional ownership, intellectual capital, corporate social responsibility (CSR), and risk management on company value in 14 banks listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023 using panel data regression analysis. The results indicate that institutional ownership has no significant effect, while intellectual capital has a negative effect, and CSR and risk management have a positive effect on firm value. The practical implications of these findings emphasize the need to optimize communication strategies to change the market's negative perception of intellectual capital investment, strengthen the implementation of sustainable CSR to build stakeholder loyalty and investor confidence, integrate risk management into business strategies to reduce uncertainty and increase transparency, and focus on internal governance mechanisms and regulatory oversight as a substitute for the role of institutional investors in the banking industry